2020
DOI: 10.1111/zsc.12423
|View full text |Cite
|
Sign up to set email alerts
|

From five to one: Sandyella species (Palaemonidae) are distinct ontogenetic stages of a single species

Abstract: The palaemonid genus Sandyella includes S. tricornuta (Isla María Madre, Mexico), S. mclaughlinae, S. bicornuta, S. quadricornuta and S. sexicornuta (Clipperton Island, France). These species were first described in the genus Chacella based on collections of few individuals and limited to no ecological information. Sandyella was later erected to differentiate Chacella kerstitchi from Chacella tricornuta and Chacella mclaughlinae. The remaining three Chacella species (<3 mm cephalothorax length) were later a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…It is still unclear whether the small changes in S. tricornuta sex ratio vary seasonally or spatially due to spatial sex segregation, unequal production of males and females, social behavior, or differential mortality rates between sexes. However, adult females of S. tricornuta were on average larger and seem to grow faster than males (Ávila-García et al 2020). The present study demonstrated S. tricornuta has a wide spatial distribution along the islands in the Gulf of California with similar population density and sex proportion favoring encounters of the females with the males consistent with other decapod symbiont species (Correa and Thiel 2003).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is still unclear whether the small changes in S. tricornuta sex ratio vary seasonally or spatially due to spatial sex segregation, unequal production of males and females, social behavior, or differential mortality rates between sexes. However, adult females of S. tricornuta were on average larger and seem to grow faster than males (Ávila-García et al 2020). The present study demonstrated S. tricornuta has a wide spatial distribution along the islands in the Gulf of California with similar population density and sex proportion favoring encounters of the females with the males consistent with other decapod symbiont species (Correa and Thiel 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Pronounced protuberances on the cephalothorax and abdomen and a yellow coloration allow S. tricornuta to mimic black coral polyps and go unnoticed (). A recent integrative taxonomic study demonstrated, with population structure, molecular and morphological evidence, that the five species previously described in the genus Sandyella were actually distinct ontogenetic stages of the type species S. tricornuta (Ávila-García et al 2020). This implies that A. galapagensis is the habitat of a single biological species.…”
mentioning
confidence: 99%
See 3 more Smart Citations